The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1159/000201474
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Small Bowel Motor Response to Solid and Liquid Meals in Man

Abstract: Interdigestive motor activity has been studied extensively both in the human and canine small intestine. The more irregular postprandial pattern, however, has rarely been studied. In particular, physiological studies in humans are lacking. Thus it is unknown whether the physical state of a meal affects the duration of the postprandial motor activity or contractile activity during the postprandial period. 8 healthy male volunteers, aged 19-38 years, underwent a single ambulatory 24-hour manometry study. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…In a preliminary comparison ( n = 6), the values of orocaecal transit time measured by magnet tracking and by lactulose hydrogen breath test were considerably different (394 ± 76 min and 172 ± 15 min respectively) 14 . This finding is in agreement with the results obtained with 6 mm metal particles and the lactulose test 15 , and are consistent with the fact that gastric emptying of large solids and liquids (ISB) and small bowel motor activity in response to solid and liquid meals may be different 16 . The size of the magnet likely contributes to the slow transit at the pylorus and the ileocaecal function (16B).…”
Section: Discussionsupporting
confidence: 87%
“…In a preliminary comparison ( n = 6), the values of orocaecal transit time measured by magnet tracking and by lactulose hydrogen breath test were considerably different (394 ± 76 min and 172 ± 15 min respectively) 14 . This finding is in agreement with the results obtained with 6 mm metal particles and the lactulose test 15 , and are consistent with the fact that gastric emptying of large solids and liquids (ISB) and small bowel motor activity in response to solid and liquid meals may be different 16 . The size of the magnet likely contributes to the slow transit at the pylorus and the ileocaecal function (16B).…”
Section: Discussionsupporting
confidence: 87%
“…A study using solid meal demonstrated that 300 kcal diet induced more prolonged fed response duration than 150 kcal diet (mean duration 359 minutes vs. 177 minutes, respectively), whereas 600 kcal diet failed to prolong the fed pattern duration than 300 kcal diet. The amplitude of contractions was not significantly affected by the amount of meal calories 43,44. The other studies comparing different calories and diet composition in liquid solution demonstrated that fed pattern duration was significantly prolonged with 300 kcal liquid diet than water and 600 kcal meals induced higher fed pattern duration than 300 kcal.…”
Section: Discussionmentioning
confidence: 81%
“…The large initial release of the meal reduces the availability of nutrient brake triggers, permitting more rapid transit during the later phase of the meal [35]. This effect is supported by the findings of Schonfeld et al [36], who observed a shorter postprandial period of motility following a liquid compared to a solid meal. In the setting of enteral feeding, the degree of hydrolysis of the administered nutrient is also important to the magnitude of the activation of the ileal brake.…”
Section: Clinical Effects Of Altered Ileal Brake Functionmentioning
confidence: 73%